INVESTIGATION OF FACTORS DETERMINING PERFORMANCE AMONG COMPETITIVE SWIMMERS AND THEIR COACHES - Papp, Tibor; Borbély, Szilvia; Bíró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2024)
In our country, swimming is one of the most successful sports. The question arises as to what might be the key to success. What are the factors that determine effectiveness? We sought the answer to this in our research. We examined the opinions of competitive swimmers (N=63) and swimming coaches (N=27) in the Eastern Hungary region. We used a questionnaire method during the survey. We focused separately on inherited and acquired skills and the importance of the coach-athlete relationship, relying on previous literature. Based on our results, the five most important factors for success are competition and training stress tolerance, performance motivation, the ability to learn competition technique, the coach-athlete relationship, as well as parents' moral support. Based on the athletes' opinion, the most decisive factor in their success is the coach's expertise, diligence, internal motivation, and parents' support.